(untitled) (Research, Society and Development, 2022)
This study aims at the metaparadigms in the quality of life of the elderly, describing the current situation of the elderly referred by nurses, including the relevance of nursing advice to this population, as well as analyzing the sociodemographic factors and the importance of attention related to the performance of informal caregivers of dependent elderly people in the community and the identification of factors associated with the condition of the environment in which the elderly live, when analyzing socioeconomic and health conditions. The present study is a descriptive field research, with a quantitative and qualitative approach, carried out with ten nurses from the UBSF of a municipality in the north of Piauí. Data and content analysis was performed. The sample consisted of eigth participants working in the ESF, the research showed satisfactory results and that everyone plays and manages to act in a context of abandonment of the elderly, as well as the particularities that age provides. proved to be satisfactory insofar as it is able to integrate information and add it to the knowledge about the subject in the professional aspect, since the professionals who answered the questionnaire were able to combine teaching and learning, seeking to have a reflection on what can be improved and introduced in the practices of adherence to the care of the elderly, in addition, it had great social and academic relevance and the analysis of this research will provide a broader perspective on the subject.